Are Chinese University Students Ready for Autonomous English Listening Practice? - Luu Thi Mai Vy; Lu Jinming (Studies in Self-Access Learning Journal, 2024)
Given the growing emphasis on autonomous learning within language education, comprehending students’ perspectives, incentives, and cognizance about autonomous listening becomes imperative for the formulation of effective pedagogical approaches. This study seeks to examine the readiness of Chinese university students to engage in autonomous English listening practice. The research employed a questionnaire-based methodology administered to a sample of 200 Chinese university students. The survey focused on gauging students’ perspectives on autonomous English listening practice, examining their level of motivation, and assessing their awareness of their capabilities in handling autonomous listening. The study revealed that Chinese university students generally recognize the prospects and promises of autonomous English listening. Notably, students exhibited increased motivation for autonomous listening provided that they were given teacher guidance and a certain level of pressure. Additionally, the findings indicated that students possess a relatively high level of awareness regarding their capabilities to engage in autonomous listening practices. This research contributes to the literature on language education by providing insights into the readiness of Chinese university students for autonomous English listening practice. The identified factors influencing motivation and awareness shed light on the potential success of implementing autonomous listening strategies. Educators and policymakers can benefit from these findings to enhance English listening instruction methodologies and better meet the needs of students in the ever-evolving landscape of language education.